2013
DOI: 10.1038/ejhg.2013.207
|View full text |Cite
|
Sign up to set email alerts
|

A novel intermediate mucolipidosis II/IIIαβ caused by GNPTAB mutation in the cytosolic N-terminal domain

Abstract: Mucolipidosis (ML) II and ML IIIa/b are allelic autosomal recessive metabolic disorders due to mutations in GNPTAB. The gene encodes the enzyme UDP-GlcNAc-1-phosphotransferase (GNPT), which is critical to proper trafficking of lysosomal acid hydrolases. The ML phenotypic spectrum is dichotomous. Criteria set for defining ML II and ML IIIa/b are inclusive for all but the few patients with phenotypes that span the archetypes. Clinical and biochemical findings of the 'intermediate' ML in eight patients with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…Interestingly, a recent study reported that MLIII αβ patients with the K4Q mutation share a specific phenotype, one that is intermediate between MLII and MLIII αβ (8). Both of these lysosomal storage disorders are caused by mutations in GNPTAB, but MLII patients have a greater loss of phosphotransferase activity, which results in a more severe phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study reported that MLIII αβ patients with the K4Q mutation share a specific phenotype, one that is intermediate between MLII and MLIII αβ (8). Both of these lysosomal storage disorders are caused by mutations in GNPTAB, but MLII patients have a greater loss of phosphotransferase activity, which results in a more severe phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the effect of two missense mutations in the N-terminal cytoplasmic tail of the α subunit of phosphotransferase, Lys4Gln (K4Q) and Ser15Tyr (S15Y) (6)(7)(8), was investigated (Fig. 1A).…”
mentioning
confidence: 99%
“…However, the Tomatsu et al study only included 11 samples, and the type of ML, or clinical severity, was not indicated. We analyzed urine KS in 51 samples from ML patients with a well-defined clinical phenotype and a confirmed diagnosis of either ML II, ML II/III, or ML III (Leroy et al 2014;Lyseng-Williamson 2014). Urine KS was elevated in all samples from patients with ML II or ML II/III and the average urine KS level in these patients (fourfold increase relative to age-matched controls) was approximately the same as that in MPS IVA patients (4.7-fold increase).…”
Section: Discussionmentioning
confidence: 99%
“…29 Patients with mucolipidosis II usually have a short lifespan, commonly resulting in death in early childhood because of cardiorespiratory problems. [35][36][37] Cardiorespiratory abnormalities are similar to those seen in MPS I (Hurler syndrome), including cardiac valve problems, thickening of the airways and thoracic cage stiffening. 35 Other clinical similarities between mucolipidosis II and MPS I may include dysostosis multiplex (Figure 10), short stature and coarse facies.…”
Section: -34mentioning
confidence: 67%
“…This causes a deficiency in N-acetylglucosamine-1 phosphotransferase, which results in lysosomal acid hydrolase enzymes lacking a normal recognition phosphate group and abnormally accumulating in the extracellular space rather than the lysosome. 35 Mucolipidosis II has autosomal recessive inheritance, with a worldwide prevalence of 0.15/100 000live births. 29 Patients with mucolipidosis II usually have a short lifespan, commonly resulting in death in early childhood because of cardiorespiratory problems.…”
Section: -34mentioning
confidence: 99%